Elements of Promotion Mix: Sales Promotion - Kelesbayev, D.N.; Jazykbayeva, B.K.; Ayazhanov, K.S.; Ersoy, A.E. (BUKETOV BUSINESS REVIEW, 2018)
In this study, a deep literature search was conducted to get rid of concept confusion in promotion mix. In the naming of elements of promotion mix, concept expressions that create confusion have been examined in detail and discussed in various comparative terms, and basic concepts with wide meaningful various actions have been proposed. More than 20 years on marketing, research and publications have dealt with research problems based on marketing mix and have mostly examined marketing processes. However, the types or elements of the marketing mix that are important for both the enterprises and the consumers are not analyzed too deeply, and different expressions or concepts are used in the analyzed sources. For example, when we study literature related to marketing used as a resource at our universities, there is a confusion of concepts when naming and ordering promotion mix which is an element of marketing mix. The terms which are used as promotion mix or promotion methods or tools, promotion styles, promotion procedures, promotion decisions; sales development or sales promotion or sales whetstone, sales incentive, other sales efforts; public relations or publicity, advertisement, publication by academicians who contribute to the development and expansion of marketing literature are confusion of words in naming promotion mix as well as the naming of promotion mix elements. In this study, a deep literature search was conducted to get rid of concept confusion in promotion mix. In the naming of elements of promotion mix, concept expressions that create confusion have been examined in detail and discussed in various comparative terms, and basic concepts with wide meaningful various actions have been proposed.